Notes sur la part d’imitation dans l’innovation en architecture - Rémi Laporte (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Does an architect become innovative when they exhibit esthetically creative work, when they use new materials or when they engage unusual methods ? In this article, we hypothesize that an innovation process to which a conception of architecture participates can borrow less overt pathways of imitation, such as those defined by Quatremère of Quincy in the 19th century. In confronting this assumption – which is done by, on the one hand, addressing recent definitions of these notions and, on the other, analyzing the windows that have been conceived by seven current architects working on collective housing operations – we seek to identify how innovation and imitation can articulate themselves within architecture as well as the ways in which they can evolve in the work of conception.